2021
DOI: 10.1007/s00330-021-07882-1
|View full text |Cite
|
Sign up to set email alerts
|

Focal pericoronary adipose tissue attenuation is related to plaque presence, plaque type, and stenosis severity in coronary CTA

Abstract: Objectives To investigate the association of pericoronary adipose tissue mean attenuation (PCATMA) with coronary artery disease (CAD) characteristics on coronary computed tomography angiography (CCTA). Methods We retrospectively investigated 165 symptomatic patients who underwent third-generation dual-source CCTA at 70kVp: 93 with and 72 without CAD (204 arteries with plaque, 291 without plaque). CCTA was evaluated for presence and characteristics of CAD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
(61 reference statements)
2
22
0
Order By: Relevance
“…The lesion-specific PCAT-MA was higher in noncalcified and mixed plaques compared to calcified plaques. These results suggest that lesion-specific PCAT-MA is related to plaque development and vulnerability [41]. In patients with acute myocardial infarction (MI), PCAT attenuation did not differentiate between the coronary segments with and without culprit lesions, but PCAT volume was strongly and independently associated with culprit lesions [42].…”
Section: Coronary Artery Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…The lesion-specific PCAT-MA was higher in noncalcified and mixed plaques compared to calcified plaques. These results suggest that lesion-specific PCAT-MA is related to plaque development and vulnerability [41]. In patients with acute myocardial infarction (MI), PCAT attenuation did not differentiate between the coronary segments with and without culprit lesions, but PCAT volume was strongly and independently associated with culprit lesions [42].…”
Section: Coronary Artery Diseasementioning
confidence: 98%
“…Patients with higher visceral fat had a greater total plaque volume and a greater level of low-attenuation plaques [40]. Another study assessed the PCAT mean attenuation (PCAT-MA) based on CT as a measure of inflammation in EAT in patients with CAD [41]. PCAT-MA was higher in coronary arteries with plaque compared to vessels without plaque.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…In recent years, the pericoronary fat attenuation index (FAI), which is measured using coronary CT angiography (CCTA) images, can be used to reflect pericoronary inflammation [2,3]. Recent studies have shown that pericoronary adipose tissue (PCAT) participates in the process of coronary inflammation and is significantly related to the type of plaque and degree of stenosis [4][5][6]. One CRISP study showed that an FAI of > − 70.1 HU was associated with a greater risk for cardiac mortality, which could improve the prediction of a heart disease risk [7].…”
Section: Introductionmentioning
confidence: 99%
“…We thus suggest that measurements of EAT attenuation on unenhanced images and calculation of the FAI from contrast-enhanced images should be performed at 70 keV. Measurements performed at 70 keV may also be most useful for comparisons with other CT systems as well as with results of prior studies that used polychromatic images for these calculations [5][6][7][8][9].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Vascular inflammation is thought to play a key role in the pathogenesis and progression of CAD. The appearance of the epicardial adipose tissue (EAT) on CT has recently been identified as a noninvasive marker of vascular inflammation, as cytokines released from the inflamed vessel segment may affect the composition of EAT through paracrine effects [2,[5][6][7][8][9]. The fat attenuation index (FAI) is a CTA-derived metric of fat attenuation determined for predefined segments of the coronary artery tree, facilitating the detection of coronary inflammation.…”
Section: Introductionmentioning
confidence: 99%